1989
DOI: 10.1136/thx.44.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Uvulopalatopharyngoplasty in severe idiopathic obstructive sleep apnoea syndrome.

Abstract: Eleven patients with severe obstructive sleep apnoea syndrome, which was fully reversed by treatment with nasal continuous positive airways pressure, underwent uvulopalatopharyngoplasty. All patients were followed for at least 12 months after surgery. One patient with large tonsils was cured. Of the remaining 10 patients, two showed minimal objective improvement at 12 months and the rest were unchanged. Four patients subsequently developed cardiac failure due to obstructive sleep apnoea. Thus uvulopalatopharyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 20 publications
0
19
2
1
Order By: Relevance
“…Nevertheless, subjects having a TAI less than 40 had the greatest chance of benefiting from UPPP. As reported by Walker [12], patients with higher TAI were not always cured by surgery. This does not mean that patients with higher TAI are ineligible for UPPP since surgery never worsens TAI nor does it alter the effectiveness of continuous positive airway pressure (CPAP) therapy, the recommended treatment for SAS [20].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, subjects having a TAI less than 40 had the greatest chance of benefiting from UPPP. As reported by Walker [12], patients with higher TAI were not always cured by surgery. This does not mean that patients with higher TAI are ineligible for UPPP since surgery never worsens TAI nor does it alter the effectiveness of continuous positive airway pressure (CPAP) therapy, the recommended treatment for SAS [20].…”
Section: Discussionmentioning
confidence: 65%
“…Some fac tors such as obesity [6,7,10] seem to be critical for success. Recently, Walker et al [12] pointed out that UPPP fails in patients with a high number of apneas. Thus it would be useful to predict the outcome of UPPP.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on UA surgery indicate a worse outcome in patients with severe OSAHS in terms of apnoea severity [3,59,60]. When looking to the pathophysiology of OSAHS and UA collapsibility, this can be easily understood.…”
Section: Osahs Severitymentioning
confidence: 98%
“…These subjects may be identified from radiological studies of the airway [44] or by fibreoptic endoscopy during sleep. Symptomatic improvement is to be expected in appropriate subjects, but objective reduction in the severity of the OSA is often less impressive [86,107] and, more importantly, nCPAP is no longer effective. The procedure is thus reserved for patients with Grades 0 and 1 disease who are not obese [107].…”
Section: Treatmentmentioning
confidence: 99%
“…Symptomatic improvement is to be expected in appropriate subjects, but objective reduction in the severity of the OSA is often less impressive [86,107] and, more importantly, nCPAP is no longer effective. The procedure is thus reserved for patients with Grades 0 and 1 disease who are not obese [107]. A recent survey has shown that the life expectancy of patients who have undergone UPPP is no different from untreated patients with OSA [45].…”
Section: Treatmentmentioning
confidence: 99%